Importin 7 enhances protective autophagy induced by nuclear translocation of homeobox A10 in oral squamous cell carcinoma: IPO7 enhances autophagy in OSCC - Chen, Shanshan; Pan, Jianbo (Cellular and Molecular Biology, 2024)
Oral squamous cell carcinoma (OSCC) is a common malignant tumor. Importin7 (IPO7) is responsible for nucleoplasmic transport of RNAs and proteins, and it has been confirmed to be involved in the development of human cancers. This study aimed to explore the function and mechanism of IPO7 in OSCC. IPO7 expression in tissues and cells was determined by RT-qPCR. Cell proliferative, migratory, and invasive capabilities were detected through transwell assay and colony formation assay. Mice xenograft models were established for evaluating tumor growth. Autophagy was estimated by the LC3 levels in cells through western blot and immunofluorescence (IF). Western blot was utilized to detect the key proteins in PERK/EIF2AK3/ATF4 pathway for assessing the endoplasmic reticulum stress (ERS). The interaction of IPO7 and homeobox A10 (HOXA10) was tested by GST pull-down assay and Co-IP assay. ChIP assay and luciferase reporter assay were utilized to determine the combination of HOXA10 and EIF2AK3. We proved that IPO7 was upregulated in OSCC tissues and cells, and its depletion reduced cell proliferation, migration, invasion and tumor growth. Furthermore, LC3 expression in cells was found to be reduced by IPO7 knockdown. IPO7 promoted OSCC tumor metastasis by activating autophagy. Additionally, we discovered that IPO7 could regulate ERS by activating the PERK/ATF4 pathway. EIF2AK3 upregulation can promote cell autophagy. Furthermore, IPO7 was proven to promote nuclear translocation of HOXA10 in cells. EIF2AK3 promoter can bind to HOXA10. Rescue assay confirmed that HOXA10 upregulation can reverse the effect of IPO7 silencing on OSCC progression. IPO7 can enhance proliferation, migration, invasion, and autophagy by nuclear translocation of HOXA10 and the activation of EIF2AK3/ATF4 pathway in OSCC.